Szczęście, przypadek czy ciężka praca i ambicja? Uczniowie szkół podstawowych o uwarunkowaniach sukcesu zawodowego - Kozielska, Joanna (Rocznik Pedagogiczny, 2020)
The text presents chosen results from research over the choices, aspirations and educational and career plans of young people (including some aspect of the perception of success). The chosen modules of the survey conducted in 2020 in a medium-sized city (approx. 80,000 inhabitants) are presented. The research goals were as follows: to characterize aspirations and plans as well as ed- ucational and professional choices made by young people; to present their opinions on the cate- gory of ‘success’ (including professional success) with its determinants; to characterize factors on educational paths of young people which enable or disable them to achieve professional success (technical, vocational schools vs general secondary schools) and prestigious versus non-prestigious professions; and to characterize the process of career counselling (students evaluation of the process and their expectations toward it). Previous studies in this field have shown that, for example, personality traits are poor predictors of entrepreneurial behaviour, while beliefs and judgments about one’s self and the world may be a determinant of success. Therefore, it can be assumed that positive beliefs about the determinants of success, such as optimism, hope for success, will contribute to a more positive perception of the transition process from education to the labour market. Importantly, the way of perceiving the deter- minants of success determines the adoption of a passive versus active attitude in shaping one’s fate. Therefore, the author of the article is interested in the way, that primary school students perceive the life and professional success (the dimension which they use to identify success or withdrawn from this identification), as well as in the way they perceive the factors that determine it. Those students’ perceptions may determine their attitudes towards shape of their lives.